Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s42003-021-01950-4
|View full text |Cite
|
Sign up to set email alerts
|

Kindlin-2 mediates mechanotransduction in bone by regulating expression of Sclerostin in osteocytes

Abstract: Osteocytes act as mechanosensors in bone; however, the underlying mechanism remains poorly understood. Here we report that deleting Kindlin-2 in osteocytes causes severe osteopenia and mechanical property defects in weight-bearing long bones, but not in non-weight-bearing calvariae. Kindlin-2 loss in osteocytes impairs skeletal responses to mechanical stimulation in long bones. Control and cKO mice display similar bone loss induced by unloading. However, unlike control mice, cKO mice fail to restore lost bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 89 publications
1
26
0
Order By: Relevance
“…Interestingly, our previous study has shown that deletion of Kindlin-2 in Dmp1-expressing mature osteoblasts and osteocytes causes decreased bone mass and abnormal bone remodeling by reducing osteoblast but increasing osteoclast formation and function [ 22 ]. We further demonstrate that Kindlin-2 in osteocytes can modulate PTH1R signaling and mediate mechanotransduction to regulate bone mass and homeostasis [ 23 , 25 ]. Thus, results from this study and our previous studies provide an integrated view on the roles of Kindlin-2 expression in osteoblastic lineage cells in regulation of bone mass accrual and homeostasis in mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, our previous study has shown that deletion of Kindlin-2 in Dmp1-expressing mature osteoblasts and osteocytes causes decreased bone mass and abnormal bone remodeling by reducing osteoblast but increasing osteoclast formation and function [ 22 ]. We further demonstrate that Kindlin-2 in osteocytes can modulate PTH1R signaling and mediate mechanotransduction to regulate bone mass and homeostasis [ 23 , 25 ]. Thus, results from this study and our previous studies provide an integrated view on the roles of Kindlin-2 expression in osteoblastic lineage cells in regulation of bone mass accrual and homeostasis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, Kindlin family proteins have three members, i.e., Kindlin- 1, -2 and -3, encoded by genes Fermt1 , Fermt2 and Fermt3 , respectively [ [18] , [19] , [20] ]. Kindlin-2 has been reported to be involved in regulation of the development and homeostasis of multiple organs and tissues, including skeleton, kidney, heart, pancreas, adipose tissue, small intestine testicle, and neural system, through both integrin-dependent and integrin-independent mechanisms [ [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] ]. For example, Kindlin-2 expression in Prx1-expressing mesenchymal progenitors is essential for mesenchymal cell differentiation and early skeletal development [ 21 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of microtubules resulted in a blunted decrease in sclerostin expression upon mechanical loading [ 76 ]. Similarly, Kindlin-2, a protein responsible for cytoskeleton organization and the formation of focal adhesions, was essential to the suppression of sclerostin expression through inhibiting Smad2/3 signaling [ 77 ]. These findings again confirm the role of the cytoskeleton in mechanical sensing.…”
Section: Osteocyte Dysfunctionmentioning
confidence: 99%
“…Recently, increasing attention has been paid to its roles in control of organogenesis and homeostasis through both integrin-dependent and integrin-independent mechanisms (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). We recently demonstrate that Kindlin-2 plays critical roles in regulation of skeletal development and bone remodeling through distinct molecular mechanisms (41)(42)(43)(44). However, it is not known whether Kindlin-2 has a role in articular cartilage homeostasis and whether alterations in its expression in articular chondrocytes are involved in OA initiation and progression.…”
Section: Introductionmentioning
confidence: 99%